Emergency medication support service: Filling the overlooked gap for those under home quarantine during the Coronavirus pandemic A view from the Hong Kong Red Cross (Branch of the Red Cross Society of China) (International Journal of First Aid Education)
Covers the qualifications and process of how the Hong Kong Red Cross (HKRC) in collaboration with the Auxiliary Medical Service (AMS) collected prescription medicines for people under 14-day home quarantine, as well as other services to vulnerable community groups, filling a gap in the Hong Kong Government's quarantine grocery delivery service.